If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2) = 11 Reorder the terms: 2(2 + x) = 11 (2 * 2 + x * 2) = 11 (4 + 2x) = 11 Solving 4 + 2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2x = 11 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 11 + -4 2x = 11 + -4 Combine like terms: 11 + -4 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5
| -6-4(x+7)=22 | | 6x+5x+3+7=7x+4+3x | | x^3=-16x | | 45x^2-24x+32=0 | | 4x-5x*2=33 | | 3(c-2)-3=-15 | | 4x+2=5y+1 | | -3x-x+3=-5 | | 10x+7.5y=420 | | 8x-17=5x+13 | | h=-36t^2+gt+d | | y-8=-6(x+1) | | 4eX=20 | | 7x+2y+4=9+11y-x | | 5*4+20= | | -15=y+82 | | 4x^2-19x-52=0 | | -9=w-13 | | 2(x-9)=7 | | 7x+10=10x+7 | | 8=y+14 | | 2.7x+142=3571 | | 5*21+20+8*21-100= | | 2.7x+142=7000 | | 8+4s=-16 | | x^2+2x-400=0 | | y=(x-3)(x-9) | | 7+2y=y | | -8v-3=5v^2 | | 8x^3(9x^2-6x+8)= | | 6u-w=u-4w | | 3x-4y=16ni |